Nutritional Culture: the fastest solution to lessen poverty - Jara Guerrero, Juan Ariel (2013)
The majority of the population , especially maternal populationchild and geriatric , has increasingly poorer health due to the intake increase of harmful nutrients that alter the expression of their genes to damage your hormonal environment, while increasing diseaseinfectious almost disappeared , cancer and shooting chronic diseases, is now emerging a new syndrome: Insulin resistance is the clearest risk factor cardiovascular . Thanks to excess "empty" calories , occupied the first place inLatin America in malnutrition and obesity and diseasehypertensive pregnancy is the leading cause of maternal death in Essalud at the same time continues increasingcongenital malformations, maternal morbidity and mortality andperinatal , degenerative diseases and dementia , knowingthat preventing abdominal obesity would reduce this alarmingincrease. Meanwhile, more than 85% of geriatric patientshave malnutrition in the chaotic system of Health (MOH ) andalmost 75 % in the Social Security System Essalud simply by a nonexistent real and primary prevention. In all three regions of the country , spending money for consumptionsweets and soft drinks is incredibly high in proportionwith low incomes , while still increasing allcardiovascular and degenerative diseases. Improving the nutritional culture in our country , we will improve your healthMental and comprehensive , we will increase our productivity and creategreater wealth.So today is postponed the realization of a programNutrition Education and Culture at all levels .